Variation in nuclear size and PD-L2 positivity correlate with aggressive chromophobe renal cell carcinoma - Mostafa, Mohamed E; Abdelkader, Amrou; Kuroda, Naoto; Pérez-Montiel, Delia; Banerjee, Anjishnu; Hes, Ondrej; Iczkowski, Kenneth A (Annals of diagnostic pathology, 2018)
Chromophobe renal cell carcinoma (CRCC) is not amenable to International Society for Urologic Pathology-endorsed nucleolar grading. Novel grading approaches were proposed, but the rarity of adverse pathology hampers their discriminatory value. We investigate simple linear micrometer measurements and a proposed immunostain in CRCCs. 32 patients' CRCCs were studied: 12 adverse cases (stage pT3, recurrence, or metastasis), 15 controls (stage ≤pT2, no recurrence or metastasis after >3 years), and 8 metastases (3 were paired with primary adverse cases). The ratio of greatest dimensions of largest and smallest nuclei, in each of 5 "worst" high-power fields, excluding those with degenerative features, was designated variation in nuclear size (VNS). Percent multinucleate cells (PMC) were also counted. Mouse anti PD-L2 monoclonal antibody immunostaining was performed. Mean VNS measured in adverse primary and control primary tumors were 3.7 ± 0.5 and 2.4 ± 0.4 respectively (P < .001), and 3.4 ± 0.4 for metastases (P < .001). Optimal VNS cut-off was 2.5, with sensitivity and specificity 0.85 and 0.81, respectively. PMCs were 6.0 ± 3.0 for adverse group, 5.7 ± 2.7 for controls, and 4.1 ± 1.6 for metastases (P = NS). PD-L2 could not discriminate adverse versus good primary tumors (χ21.6, P = .2), but was higher in metastases (χ2 6.9, P < .01), or metastases plus adverse primary tumors (χ2 4.8, P = .03), compared to good-pathology primary tumors. In conclusion, VNS is an easily obtained measurement that can predict adverse behavior of chromophobe RCC, and may impart value for needle biopsy reporting and the choice of active surveillance. PD-L2 was elevated in metastases but was less useful for primary tumors.
Keywords: dospělí; Animals; Female; Cell Nucleus Size; Chromophobe; antigeny CD273; Adult; mladý dospělý; ženské pohlaví; Antibodies, Monoclonal; lidé; Cell Nucleus; Mice; velikost buněčného jádra; karcinom z renálních buněk; Aged, 80 and over; myši; prognóza; Kidney Neoplasms; Carcinoma, Renal Cell; buněčné jádro; Nuclear size variation; Male; Aged; Programmed Cell Death 1 Ligand 2 Protein; Young Adult; Prognosis; Renal cell carcinoma; nádory ledvin; monoklonální protilátky; lidé středního věku; senioři nad 80 let; senioři; zvířata; mužské pohlaví; PD-L2; Middle Aged; Humans